2018
DOI: 10.1253/circj.cj-17-0369
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Preoperative Frailty and Mortality in Patients With Critical Limb Ischemia Following Infrainguinal Bypass Surgery ― Usefulness of the Barthel Index ―

Abstract: Background: Most patients with critical limb ischemia (CLI) exhibit severe comorbidities accompanied by frailty. This study assessed and risk-stratified mortality after infrainguinal bypass (IB) in CLI and investigated the effects of frailty. Methods and Results:The study retrospectively reviewed 107 consecutive CLI patients who had undergone de novo IB due to atherosclerotic disease. Data regarding patient age, comorbidities, laboratory data, and functional status were collected; functional status was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…1). Seven multi-domain tools were adopted in 12 studies to assess frailty status before vascular procedures: the Groningen Frailty Indicator (GFI), 8 Edmonton Frail Scale (EFS), 31 modified Frailty Index (mFI), 13,14,26,29,30 Barthel Index (BI), 15 Addenbrooke's Vascular Frailty Score (AVFS), 28 Ruptured Aneurysm Frailty Score (RAFS), 27…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Seven multi-domain tools were adopted in 12 studies to assess frailty status before vascular procedures: the Groningen Frailty Indicator (GFI), 8 Edmonton Frail Scale (EFS), 31 modified Frailty Index (mFI), 13,14,26,29,30 Barthel Index (BI), 15 Addenbrooke's Vascular Frailty Score (AVFS), 28 Ruptured Aneurysm Frailty Score (RAFS), 27…”
Section: Resultsmentioning
confidence: 99%
“…35 Six studies were conducted in patients who underwent major vascular surgery, 7,8,28,30,31,34 nine studies in patients with AAA, 11,12,14,27,33,36e39 and 10 studies in patients with LEAD. 10,13,15,25,26,29,32,33,35,40 The basic characteristics of the included studies are given in Table 1.…”
Section: And Criticalmentioning
confidence: 99%
“…29 A study of patients with severe limb ischemia also compared patients with high BI and low BI to determine whether BI is useful for risk stratification after bypass surgery. 30 It is well known that the dependence of the elderly on the abilities of daily living increases with age. A study on the factors influencing the daily life of elderly people in China found that older age was a relevant factor for the loss of activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] This study adds to a growing body of evidence relating to the value of frailty as a predictor of mortality risk across a range of populations and settings. 23,[27][28][29][30][31][32] Implications for research and practice There are compelling reasons to avoid unnecessary hospitalisation in older people, including the risks of deconditioning and iatrogenic harm. 8 However, the data presented in this study demonstrate poor outcomes even among frail older people discharged from hospital after brief (<72 hours) stays, suggesting that early discharge is not (on its own) sufficient to meet the needs of these patients.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%